Feminisms and the Qur’anic Text - EL-Naggar, Nehal (Advances in Social Sciences Research Journal, 2019)
Are Feminism and Islam mutually exclusive terms? Actually, they are not. As the process of modernization spreads around the world, Muslim women have asked various unpopular questions concerning the interaction between Islam and Feminism. The result has been the construction of various feminist traditions within Islam. This essay seeks to examine the root causes behind various Islamic feminist reformers. The dawn of the nineteenth century marked the beginning of an epoch of worldwide social change that has continued to challenge the religious and social basis of all societies to this day. European colonial powers formed the political and economic ideological framework that was to encroach upon the Islamic world. The gradual emergence of the global economy and the political ascendancy of the West dictated a global trend that was not easy for non-Western nations to avoid. These changes have invariably been multidimensional in nature; from the emergence of territorial states in their current format to educational reforms. One of the areas to undergo a radical transformation is relation between the sexes, as women searched for their identity and place in the new world.